Anti-inflammatory Activity of a Polypeptide Fraction From Achyranthes bidentate in Amyloid β Oligomers Induced Model of Alzheimer’s Disease - Ge, Xiangyu; Wang, Yitong; Yu, Shu; Cao, Xuemin; Chen, Yicong; Cheng, Qiong; Ding, Fei (Frontiers in Pharmacology, 2021)
Neuroinflammation plays a crucial role in neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD), and anti-inflammation has been considered as a potential therapeutic strategy. Achyranthes bidentate polypeptide fraction k (ABPPk) was shown to protect neurons from death and suppress microglia and astrocyte activation in PD model mice. However, how ABPPk regulates neuroinflammation to exert a neuroprotective role remains unclear. Toxic Aβ oligomers (AβOs) can trigger inflammatory response and play an important role in the pathogenesis of AD. In the present study, for the first time, we investigated the effects and underlying mechanisms of ABPPk on neuroinflammation in AβOs-induced models of AD. In vitro, ABPPk pretreatment dose-dependently inhibited AβOs-induced pro-inflammatory cytokine release in BV2 microglia and reduced the neurotoxicity of BV2 microglia-conditioned media in hippocampal neurons. Furthermore, ABPPk down-regulated the phosphorylation of NF-κB p65 and the expression of NLRP3. In vivo, ABPPk pre-administration significantly improved locomotor activity, alleviated memory deficits, and rescued neuronal loss in the hippocampus of AβOs-injected mice. ABPPk inhibited the activation of microglia in hippocampal CA3 region and suppressed the activation of NF-κB as well as the expression of NLRP3 in the brain after AβOs injection. ABPPk hindered the release of pro-inflammatory factors and promoted the release of anti-inflammatory factors in the brain. Notably, the polarization experiment on BV2 microglia demonstrated that ABPPk inhibited M1-phenotype polarization and promoted M2-phenotype polarization by activating the LPS-inhibited autophagy. Taken together, our observations indicate that ABPPk alleviates AβOs-induced neuroinflammation by regulating microglial polarization and thus propose ABPPk as a potential treatment for neurodegenerative disease such as AD.